Development of a Data Portal System for Governance in Berau - Hadi Firmansyah; Eko Junirianto; Eny Maria (TEPIAN, 2024)
The development of a Data Portal System for Berau Governance addresses the need for an integrated platform to effectively manage and disseminate government data. This system aims to enhance transparency, accountability, and public access to diverse datasets in alignment with the One Data Indonesia initiative. The portal consolidates various data categories, including news, announcements, agendas, publications, downloads, infographics, and visualizations, into a single platform, streamlining data access for both government agencies and the public. The system was developed using the Rapid Application Development (RAD) methodology, enabling iterative prototyping and quick adjustments based on feedback from key stakeholders. This approach ensured the system could meet the dynamic requirements of the government while remaining adaptable to future needs. The Laravel framework was chosen for its flexibility, scalability, and security features, allowing the system to provide a responsive, user-friendly experience while maintaining high levels of data integrity.The Data Portal System significantly improves the local government’s ability to manage and share information, fostering greater civic engagement and enhancing public trust in governance processes. Furthermore, the system facilitates more efficient public service delivery by making key data accessible in a structured and intuitive format. Regular assessments and updates are recommended to ensure the system continues to align with evolving user needs and governmental policies, further advancing data governance in Berau Regency.